(untitled) (Journal of Artificial Intelligence & Research, 2023)
More so, as the adoption of cloud computing continues to grow, there are more compliance demands, higher expenses, and continued emergence of new threats. Previous concepts in cloud security strategies mostly included compliance with regulations, while with AI’s incorporation there is a shift that addresses the compliance aspect with equal consideration for cost containment. In the following paper, the author seeks to understand how AI can help advance current cloud security paradigms and show how compliance, resources, and security costs are not a hindrance to efficient and effective delivery of cloud services. Enthusiastically, the paper shows strong AI-based solutions that equal the peculiar ideas of various compliance monitoring, threat detection, automated response to an incurrence or surge in criminal incidents, and several predictive analytics. These results propose that AI can considerably decrease the personnel and systemic loads, costs, and dangers and empower organizations to be more proactive in cloud safety. This paper also explains the specific issues regarding the use of AI in cloud security and the privacy issues arising from this practice, modeling the current problems of AI in terms of further development of technologies for AI-based optimization of cloud security.